2023
DOI: 10.1021/acsbiomaterials.3c00506
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Osteogenic Potential of Noggin Knockout C2C12 Cells on BMP-2 Releasing Silk Scaffolds

Anıl Sera Çakmak,
Sümeyra Fuerkaiti,
Dilara Karagüzel
et al.

Abstract: The CRISPR/Cas9 mechanism offers promising therapeutic approaches for bone regeneration by stimulating or suppressing critical signaling pathways. In this study, we aimed to increase the activity of BMP-2 signaling through knockout of Noggin, thereby establishing a synergistic effect on the osteogenic activity of cells in the presence of BMP-2. Since Noggin is an antagonist expressed in skeletal tissues and binds to subunits of bone morphogenetic proteins (BMPs) to inhibit osteogenic differentiation, here Nogg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…β-oxidation is the main process of fatty acid oxidation, in which fatty acids are activated to generate fatty acyl-CoA; the activated fatty acyl-CoA enters the mitochondria and is oxidized, being the main source of biological energy for the body or tissues [ 34 ]. Studies have shown that ACADL, ACADM, and CPT2 participate in fatty acid metabolism in porcine skeletal muscle and are associated with IMF deposition and muscle development in pigs [ 35 , 36 ]. In the present study, the expression levels of ACADL, ACADM, and CPT2 in the LD240 group were significantly higher than those in the LD120 group.…”
Section: Discussionmentioning
confidence: 99%
“…β-oxidation is the main process of fatty acid oxidation, in which fatty acids are activated to generate fatty acyl-CoA; the activated fatty acyl-CoA enters the mitochondria and is oxidized, being the main source of biological energy for the body or tissues [ 34 ]. Studies have shown that ACADL, ACADM, and CPT2 participate in fatty acid metabolism in porcine skeletal muscle and are associated with IMF deposition and muscle development in pigs [ 35 , 36 ]. In the present study, the expression levels of ACADL, ACADM, and CPT2 in the LD240 group were significantly higher than those in the LD120 group.…”
Section: Discussionmentioning
confidence: 99%
“…Non-fusion or failed fusion after surgery is a recurring concern [9], and identifying the underlying factors has been a focal point of research. One possible explanation is linked to the intricate role of bone morphogenetic protein (BMP) antagonists secreted by the IVD itself [10,11]. These antagonists have been associated with inhibiting osteogenesis in the presence of IVD cells [12,13].…”
Section: Introductionmentioning
confidence: 99%